CHANGE OF PECTIN SUBSTANCES OF FUNCTIONAL DRINKS DURING TECHNOLOGICAL PROCESSING - Natalia Sergeevna Limareva; Valeria Nikolaevna Orobinskaya (Современная наука и инновации, 2022)
This article is about development of functional beverages based on technology using cabbage juice with apple and beetroot pectin concentrates. Data on development of technology of functional drinks on the basis of cabbage juice with the use of apple and beet pectin concentrates are presented in article. The research of content of pectin substances, change of their quantity in the course of technological processing is conducted, the functional orientation of drinks is defined, optimum parameters of sterilization of drinks are determined.